1996
DOI: 10.1007/pl00014233
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 deficiency in adolescents and young adults with phenylketonuria

Abstract: Following several years absence from clinical follow up, an 18-year-old female on diet therapy for phenylketonuria presented with spastic paraparesis, tremor, disorientation, slurred speech, distractibility, deteriorating mental function and megaloblastic anaemia (Hb 64g/l mean corpuscular volume 121). Plasma phenylalanine levels were 100-600 mumol/l for the first 18 months of life but thereafter, because of serious psycho-social factors, > 1200 mumol/l. Her diet had strictly excluded all meats, eggs and dairy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 11 publications
1
35
0
2
Order By: Relevance
“…The results of the volumetric measurements are summarized in Table 1. These findings of Pfaendner et al [13] are in accordance with other, nonquantitative imaging studies [8,[16][17][18][19]. However, it has not been previously reported that the size of the hippocampus is reduced in PKU.…”
Section: Mr Volumetrysupporting
confidence: 82%
“…The results of the volumetric measurements are summarized in Table 1. These findings of Pfaendner et al [13] are in accordance with other, nonquantitative imaging studies [8,[16][17][18][19]. However, it has not been previously reported that the size of the hippocampus is reduced in PKU.…”
Section: Mr Volumetrysupporting
confidence: 82%
“…In our study, patients with very strict long-term diet did not show speci®c neurological impairment either. Vitamin B 12 de®ciency was also discussed as a possible cause of neurological impairment in adults with PKU [11]. In our study, vitamin B 12 de®ciency could be excluded in a subsample of seven patients with tremor by normal concentrations of plasma vitamin B 12 and urinary methylmalonic acid.…”
Section: Discussionmentioning
confidence: 94%
“…Hanley and colleagues reported that 6 (16%) out of 37 adolescent and young adult PKU patients had subnormal serum vitamin B 12 concentrations. They recommend that complete blood count, serum vitamin B 12 , and RBC folate concentrations be routinely measured in adolescents and young adults with PKU (Hanley et al 1996). Early assessment and therapy of iron deficiency may improve cognitive and behavioural outcomes of children with PKU (Acosta et al 2004).…”
Section: Organic Acidaemiasmentioning
confidence: 98%